IMAGE AND MOTIVES IN HAMZA'S DRAMAS (American Journal of Interdisciplinary Research and Development, 2024)
This article talks about the drama genre and the theme, plot and artistic function of images typical of the people's lifestyle in it. Some of Hamza's dramas are taken as examples and analyzed in detail.